2014
DOI: 10.1016/j.jacc.2013.10.087
|View full text |Cite
|
Sign up to set email alerts
|

Endocardial Ablation to Eliminate Epicardial Arrhythmia Substrate in Scar-Related Ventricular Tachycardia

Abstract: Elimination of Epi-LAVA with endocardial RF delivery is feasible and might be used first to reduce the risk of epicardial ablation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(53 citation statements)
references
References 30 publications
1
51
0
1
Order By: Relevance
“…This can be explained by the lower wall thickness encountered in ischemic scars and dysplasic right ventricular walls, as compared with the relatively preserved wall thickness in NICM. 11,29 These findings support the use of endocardial ablation as a first line strategy in ICM and ARVC, epicardial ablation being required for resistant sites only, with the use of image integration to minimize the risk of CAs and PN injury. In patients with NICM, our results suggest that a combined endocardial and epicardial ablation approach may be required in most cases.…”
Section: Strategy To Eliminate Epicardial Lavasmentioning
confidence: 67%
“…This can be explained by the lower wall thickness encountered in ischemic scars and dysplasic right ventricular walls, as compared with the relatively preserved wall thickness in NICM. 11,29 These findings support the use of endocardial ablation as a first line strategy in ICM and ARVC, epicardial ablation being required for resistant sites only, with the use of image integration to minimize the risk of CAs and PN injury. In patients with NICM, our results suggest that a combined endocardial and epicardial ablation approach may be required in most cases.…”
Section: Strategy To Eliminate Epicardial Lavasmentioning
confidence: 67%
“…Furthermore, in order to assess this potential relationship, the antecedent of prior cardiac surgery was included in the univariate analysis and, according to this study's data, it was not related with the occurrence of VT recurrence [HR 0.937(0.34-2.58); p=0.937] (table 3). A recent study has shown that epicardial substrate can be eliminated by endocardial ablation 29 . However, the same study also reported that complete elimination of epicardial substrate was achieved in only a minority of ischemic cases (22.2%); therefore, the majority of them would require an epicardial ablation to completely eliminate the epicardial substrate 29 .…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has shown that epicardial substrate can be eliminated by endocardial ablation 29 . However, the same study also reported that complete elimination of epicardial substrate was achieved in only a minority of ischemic cases (22.2%); therefore, the majority of them would require an epicardial ablation to completely eliminate the epicardial substrate 29 . In addition to this and according to the present study data, patients with transmural MI who underwent only endocardial ablation are at an increased risk of VT recurrence, despite the potential impact of the endocardial ablation in the epicardial substrate.…”
Section: Discussionmentioning
confidence: 99%
“…19 The role of epicardial mapping in guiding endocardial catheter ablation was previously reported. 10,11 In our series, only 3 patients had similar activation times from endocardium and epicardium.…”
Section: Epicardial Mapping Guiding Endocardial Ablationmentioning
confidence: 98%